A micro-grid ensuring multi-objective control strategy of a power electrical system for quality improvement. (August 2015) - Rekik, Mouna; Abdelkafi, Achraf; Krichen, Lotfi
Abstract: The increasing integration of fluctuating and NL (non-linear) loads in the main grid can introduce problems to the distribution power system quality. This study was interested in a MG (micro-grid) based on RDG (renewable distributed generator) to participate in system services and to improve the efficiency of the power electrical system. The purpose of this paper is to investigate a multi-objective control strategy for the integration of an MG into electrical network in order to ensure simultaneously active power supply, reactive power compensation, harmonic current damping and grid frequency regulation. This control is mainly composed of two parts: the first one is the "NL Loads currents identification system" used to extract the fundamental active current from the disruptive one in order to provide the required harmonic and reactive currents to the considered NL loads. The second one is the "active power transfer and frequency control algorithm" used to manage the MG in six operation modes in order to control the fundamental active power flow exchange between the MG and the electrical network making the grid frequency in an allowable range of stability. Highlights: A multi-objective control of a micro-grid to participate in various system services is proposed. This control can be applied for any types of renewable energy. An "NL Loads currents identification system" for harmonic and reactive power compensation is developed. An "active power transfer and frequency control algorithm" is also investigated.